Feeding Stimulant for Epilachna indica (Coleoptera: Coccinellidae) from the Leaf Surface of Solanum melongena - Abdullah, Fauziah; Partiban, Subramanian; Abdullah, Faizah (Malaysian Journal of Science, 2003)
A study was conducted to observe the 12 spotted lady bird beetle, Epilachna indica (Coleoptera:Coccinellidae) feeding on the eggplant Solanum melongena (Family: Solanacea) in a farm in Somme Estate, Serdang, Kedah. The study was conducted for 24 hours on 3 different days and subsequently followed by a 12 hour observation on feeding behavior conducted in the laboratory. The optimal feeding time was found to be between 0800h to 1000h and between 1700h to 2000h in the laboratory and 1700h to 2000h in the field. The leaves of Solanum melongena were collected and an ethanol extract obtained. Epilachna indica exhibited strong feeding behavior to two fractions as shown by column chromatography. Analysis of the fractions using Gas Chromatography-Mass Spectrometry gave 2-furancarboxaldehyde as the compound found in the purified extract which causes feeding behavior in Epilachna indica.